2011
DOI: 10.1136/vr.d2344
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of oestrus detection methods in dairy cattle

Abstract: Sixty-seven Holstein-Friesian cows, from 20 days postpartum, were recruited into the study and fitted with both a pedometer (SAE Afikim) and a Heatime neck collar (SCR Engineers) and allocated a heat mount detector (either scratchcard [Dairymac] or KaMaR [KaMaR]) or left with none, relying only on farm staff observation. Common production stressors and other factors were assessed to determine their impact on the ability of each method to accurately detect oestrus and to investigate effects on the frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 23 publications
0
83
2
2
Order By: Relevance
“…Increased physical activity is a secondary sign of estrus in cattle, and pedometry systems that detect changes in the number of steps per unit time have been available for many years with some adoption by the dairy industry in the United States. A new generation of electronic systems that continuously monitor physical activity in cattle (Holman et al, 2011;Jónsson et al, 2011) have been developed, and there has been rapid adoption of this technology in the United States over the past several years. Many reviews have been published on systems used to detect estrus in cattle (Nebel et al, 2000;Firk et al, 2002;Rorie et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Increased physical activity is a secondary sign of estrus in cattle, and pedometry systems that detect changes in the number of steps per unit time have been available for many years with some adoption by the dairy industry in the United States. A new generation of electronic systems that continuously monitor physical activity in cattle (Holman et al, 2011;Jónsson et al, 2011) have been developed, and there has been rapid adoption of this technology in the United States over the past several years. Many reviews have been published on systems used to detect estrus in cattle (Nebel et al, 2000;Firk et al, 2002;Rorie et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Using cow information, reproductive dynamics and economics representative for the dairy situation in the Netherlands, Inchaisri et al (2010) predicted that an improvement in the oestrus detection rate from 0.30 to 0.50 and from 0.50 to 0.70 will reduce the net economic loss by €53.29 and €11.20 per cow per year, respectively. Various oestrus detection methods aimed at improving detection rate have been developed, evaluated and compared (Diskin and Sreenan, 2000;Firk et al, 2002;Roelofs et al, 2010;Holman et al, 2011). Despite this, modern dairy farming would substantially benefit from an improved oestrus detectability via an increased expression of oestrous behaviour in cows, that is, if cows would generally show the various signs of oestrus during a longer period of time and at a higher intensity and if more cows would show standing oestrus.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies have confirmed that the measurement of the increase in the number of steps is a useful tool for the detection of oestrus, especially if associated with a specific algorithm (Moore and Spahr 1991;Lehrer et al 1992;Liu and Spahr 1993;AtTaras and Spahr, 2001;de Mol et al, 2001;Firk et al, 2002;Roelofs et al 2005). Many oestrus detection systems are used in attempt to improve conception rates, ranging from the simple visual observation of the animals to more specific systems based on the measurement of the cows' activity through pedometers or collar activity meters (Holman et al, 2011). The effectiveness of pedometer-aided detection of oestrus, when compared with visual observation, is quite variable and ranges from 60 to 100%, depending on the study (Lehrer et al, 1992).…”
Section: Introductionmentioning
confidence: 99%